Testing effects of pesticides on macroinvertebrate communities in outdoor stream mesocosms using carbaryl as example test item - Beuter, Liesa-Kristin; Dören, László; Hommen, Udo; Kotthoff, Matthias; Schäfers, Christoph; Ebke, Klaus Peter; Justus Liebig University Giessen (My University, 2019)
Background: In mesocosms, the fate and effects of chemicals can be investigated under more realistic conditions than in laboratory-scale experiments and most mesocosm studies for higher-tier risk assessment are conducted in lentic test systems. However, particularly for the assessment of EPT taxa (Ephemeroptera, Plecoptera, Trichoptera) and gammarids (Amphipoda), which are considered to be ecologically vulnerable macroinvertebrates, lotic systems seem to be more appropriate. Within this pilot study, eight newly constructed stream mesocosms were tested for their suitability in the effect assessment of plant protection products (PPP). By using the insecticide carbaryl as an example test item, five concentrations without replicates were tested under a worst case exposure scenario and three stream mesocosms served as controls.Results: 15 out of the 51 invertebrate taxa found during the study belonged to EPT taxa, while the common lotic amphipod Gammarus sp. (G. pulex and G. roesili) was the most dominant taxa. Estimation of minimum detectable differences based on mean abundances and variance of taxa in the eight mesocosms before application indicate that for five arthropoda taxa and two non-arthropoda taxa, an analysis of effects would have probably would have been possible in a typical test design for a higher-tier study with more test units. Five of these taxa were typical stream taxa, i.e. mayflies, caddisflies and gammarids. With respect to the effects of carbaryl, multivariate analysis (principal response curve) indicates long-term effects on the macroinvertebrates community over several weeks for the highest carbaryl concentration (120 microgram a.i./L). Potential effects were observed for the amphipod Gammarus sp., the mayfly Ephemera danica and the caddisfly family Limnephilidae.Conclusions: Through this study it was shown that the stream mesocosms provided suitable habitats for potential sensitive and vulnerable taxa, including those typical for lotic systems. To enable a reliable statistical analysis of the effects within the higher-tier ecological risk assessment, the number of stream mesocosms needs to be enhanced. In addition, colonisation and sampling should be improved to increase the number of taxa with sufficiently high abundances for evaluation.
Keywords: stream mesocosms; carbaryl; EPT taxa; lotic ecosystems; higher-tier risk assessment; ddc:630